The Effect of Soft Skills to Student’s Work Readiness Through Learning Achievements and on the Job Training as Interviening Variable (Empirical Studies on Accounting Major of Vocational High School Students in Tegal Regency) - Ariyanto, Agus; Wahyudin, Agus; Martono, S. (Journal of Economic Education, 2020)
The purpose of this study is to examine whether Soft Skill influences or not on Work Readiness both directly and indirectly. As in this study, Learning Achievement and On The Job Training as Intervening Variables. A total of 131 students were taken as samples by using Stratified random sampling. The statistical method used to test intervening variables uses the Path Test. The results showed that soft skills affect work readiness. And soft skills affect work readiness through learning achievement and On The Job Training as an intervening variable. Soft skills indirectly have a greater effect than directly on work readiness.